Transforming Nursing Clinical Education: The Power of Environment, Student Motivation, and Clinical Instructors - Lia Mulyati; Nur Wulan; Abdal Rohim (Fakultas Ilmu Keperawatan Universitas Indonesia, 2026)
Clinical learning is an important component in the formation of nursing students’ professional competence. The clinical environment, student motivation, and the role of clinical instructors are factors that influence the achievement of learning outcomes in nursing clinical practice. However, the relationship between these factors is still not fully understood. This study aims to examine the relationship between the clinical environment, student motivation, and the role of clinical instructors, and to determine how these three factors contribute to learning outcomes in nursing clinical practice. A quantitative design with a cross-sectional survey approach was used. The sample consisted of 117 nursing students, and data were collected through questionnaires. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results showed that the clinical environment significantly contributed to learning outcomes (p-value 0.001) and student motivation (p-value 0.040). The role of clinical instructors influenced perceptions of the clinical environment (p-value 0.001) and student motivation (p-value 0.001), but did not directly affect learning outcomes. Student motivation contributed significantly to learning outcomes (p-value 0.029). The research model demonstrated a fairly good fit with the data. The clinical environment and student motivation are essential for achieving learning outcomes in nursing clinical practice. The role of clinical instructors contributes indirectly by enhancing student motivation. Educational institutions and hospitals should collaborate to create a conducive learning environment and provide effective training for clinical instructors.